Raj revisited - Nevile, Pran (New Delhi Niyogi Books, 2012)
Two hundred years of imperial rule left a legacy of Raj literature comprising journals, diaries and travelogues, ably complemented with the visual images created by the numerous British artists, both amateur and professional. Until the late 18th century, there was no visual record of India since landscape painting did not figure in an otherwise rich Indian art. It was left to these dedicated and meticulous artists like Hodges, Daniells and Gold to amass a vast illustrative treasure ranging from the Sahib's day-to-day routine to the people of India, with their diverse customs and manners and way of life. This book is a virtual pilgrimage in to the past, a guided tour of imperial India. It is sumptuously illustrated with reproductions of the finest paintings, aquatints, engravings and lithographs, assembled for the first time in a single publication, from the collections of the libraries and museums in India, Britain and the U.S.A.
Keywords: Painting; Art; IFS as an author; Indian Foreign Service